1969
DOI: 10.1021/bi00838a045
|View full text |Cite
|
Sign up to set email alerts
|

Application of secondary .alpha.-deuterium kinetic isotope effects to studies of enzyme catalysis. Glycoside hydrolysis by lysozyme and .beta.-glucosidase

Abstract: Secondary kinetic isotope effects (a-deuterium) have been explored as a method for delineating the nature of the transition state in enzyme-catalyzed reactions. Hen egg-white lysozyme and almond @-glucosidase were chosen as enzymes for these experiments. Initially, model studies were performed on the cleavage of phenyl glucosidic bonds in acid (SN1 mechanism) and in base (sN2 mechanism). The values obtained (kH/kD = 1.13 for sN1 mechanism, ka/ko = 1.03 for S N~ mechanism) were in the anticipated range. The val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

1972
1972
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(54 citation statements)
references
References 21 publications
2
52
0
Order By: Relevance
“…Lysoryme I n an early application of secondary isotope effects to the study of enzyme reactions, Dahlquist et al showed that the lysozyme-catalyzed hydrolysis of a phenyl-8-D-glucopyranoside, containing deuterium a t C-1, is characterized by an isotope effect of 1.11. This isotope effect compares to values of 1.13 and 1.03 observed for acid (SN-1) and base (SN-2) hydrolysis (165). The similarity of isotope effects observed for the lysozyme-and acid-catalyzed reactions led Dahlquist et al to conclude considerable carbonium character at the transition state in the reaction catalyzed by lysozyme.…”
Section: B Glycosidasesmentioning
confidence: 71%
“…Lysoryme I n an early application of secondary isotope effects to the study of enzyme reactions, Dahlquist et al showed that the lysozyme-catalyzed hydrolysis of a phenyl-8-D-glucopyranoside, containing deuterium a t C-1, is characterized by an isotope effect of 1.11. This isotope effect compares to values of 1.13 and 1.03 observed for acid (SN-1) and base (SN-2) hydrolysis (165). The similarity of isotope effects observed for the lysozyme-and acid-catalyzed reactions led Dahlquist et al to conclude considerable carbonium character at the transition state in the reaction catalyzed by lysozyme.…”
Section: B Glycosidasesmentioning
confidence: 71%
“…Phillips and coworkers (17,18) have proposed a charged species, a carbonium ion, for the activated complex of lysozyme. Also, Dahlquist, Rand-Mier, and Raftery (19) have found that the lysozyme reaction has carbonium ion character. The small value found for AV* is at least consistant with the supposition that the enzyme makes no major changes in conformation when it combines with the substrate to form the activated complex.…”
Section: Resultsmentioning
confidence: 99%
“…Model building further suggested that it would be difficult to fit the monosaccharide unit occupying the D position in its most stable chair conformation into the protein superstructure without distorting the ring toward the half chair favored by the sp2 transition state. Thus, the enzyme was postulated to act in part by means of a substrate distortion mechanism, whereby part of the substrate intrinsic binding energy is by secondary hydrogen isotope effects (32,33) and by oxygen-18 leaving group kinetic isotope effects (34). The latter group concluded that the transition state for the reaction resembled a nearly fully formed oxocarbocation.…”
Section: Discussionmentioning
confidence: 99%